Low Level Primary Blast Injury in Rodent Brain - Pun, Pamela B.; Kan, Enci Mary; Salim, Agus; Li, Zhao Hui; Ng, Kian Chye; Moochhala, Shabbir M.; Ling, Eng-Ang; Tan, Mui Hong; Lu, Jia (Frontiers in Neurology, 2011)
The incidence of blast attacks and resulting traumatic brain injuries has been on the rise in recent years. Primary blast is one of the mechanisms in which the blast wave can cause injury to the brain. The aim of this study was to investigate the effects of a single sub-lethal blast over pressure exposure of either 48.9 kPa (7.1 psi) or 77.3 kPa (11.3 psi) to rodents in an open-field setting. Brain tissue from these rats was harvested for microarray and histopathological analyses. Gross histopathology of the brains showed that cortical neurons were ‘darkened’ and shrunken with narrowed vasculature in the cerebral cortex day 1 after blast with signs of recovery at day 4 and day 7 after blast. TUNEL-positive cells were predominant in the white matter of the brain at day 1 after blast and double-labeling of brain tissue showed that these DNA-damaged cells were both oligodendrocytes and astrocytes but were mainly not apoptotic due to the low caspase-3 immunopositivity. There was also an increase in amyloid precursor protein immunoreactive cells in the white matter which suggests acute axonal damage. In contrast, Iba-1 staining for macrophages or microglia was not different from control post-blast. Blast exposure altered the expression of over 5786 genes in the brain which occurred mostly at day 1 and day 4 post-blast. These genes were narrowed down to 10 overlapping genes after time-course evaluation and functional analyses. These genes pointed towards signs of repair at day 4 and 7 post-blast. Our findings suggest that the blast over pressure levels in the study resulted in mild cellular injury to the brain as evidenced by acute neuronal, cerebrovascular and white matter perturbations that showed signs of resolution. It is unclear whether these perturbations exist at a milder level or normalize completely and will need more investigation. Specific changes in gene expression may be further evaluated to understand the mechanism of blast-induced neurotrauma.